Writing extension materials - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
training workshop on writing and producing agricultural extension materials. The workshop was held in Zimbabwe from 3-15 March 1997